Isoprenoid Pyrophosphate-Dependent Transcriptional Regulation of Carotenogenesis in Corynebacterium glutamicum - Henke, Nadja A.; Heider, Sabine A. E.; Hannibal, Silvin; Wendisch, Volker F.; Peters-Wendisch, Petra (Frontiers in Microbiology, 2017)
Corynebacterium glutamicum is a natural producer of the C50 carotenoid decaprenoxanthin. The crtEcg0722crtBIYEb operon comprises most of its genes for terpenoid biosynthesis. The MarR-type regulator encoded upstream and in reverse orientation of the carotenoid biosynthesis operon has not yet been characterized. This regulator, named CrtR in this study, is encoded in many actinobacterial genomes co-occurring with terpenoid biosynthesis genes. CrtR was shown to repress the crt operon of C. glutamicum since DNA microarray experiments revealed that transcript levels of crt operon genes were increased ten to seventyfold in its absence. Transcriptional fusions of a promoter-less gfp gene with the crt operon and crtR promoters confirmed that CrtR represses its own gene and the crt operon. Gel mobility shift assays with purified His-tagged CrtR showed that CrtR binds to a region overlapping with the -10 and -35 promoter sequences of the crt operon. Isoprenoid pyrophosphates interfered with binding of CrtR to its target DNA, a so far unknown mechanism for regulation of carotenogenesis. The molecular details of protein-ligand interactions remain to be studied. Decaprenoxanthin synthesis by C. glutamicum wild type was enhanced ten to thirtyfold upon deletion of crtR and was decreased five to sixfold as result of crtR overexpression. Moreover, deletion of crtR was shown as metabolic engineering strategy to improve production of native and non-native carotenoids including lycopene, ß-carotene, C.p. 450 and sarcinaxanthin.